2015
DOI: 10.2147/ppa.s84411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pharmaceutical care on medication adherence of patients newly prescribed insulin therapy: a randomized controlled study

Abstract: BackgroundPoor adherence to insulin medications leads to a high rate of hospital admissions and poor health-related quality of life in the patients with diabetes mellitus. However, few strategies are effective and acceptable in improving medication adherence. The objectives of this study are to evaluate the effectiveness of pharmaceutical care by clinical pharmacists on medication adherence of patients newly prescribed insulin therapy.Patients and methodsA single-center, prospective randomized controlled study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 18 publications
1
32
0
6
Order By: Relevance
“…(33) einstein (São Paulo). 2020;18:1-14 Chung et al (28) Teaching hospital in Malaysia Ali et al (29) Community pharmacies in the United Kingdom Xin et al (38) Tongde Hospital, Hangzhou province, China As regards performance bias, no studies reported blinding to pharmacist's activities, and exchange of information between participants may have occurred in 14 studies conducted in a single setting, except the multicenter study by Siaw et al (33) That trial was thought to involve high risk of bias regarding blinding of participants and professionals, since participants in the Control Group were able to consult pharmacists, if required. (34) As regards detection bias, only one study reported blinding of raters, who were therefore unaware of groups being evaluated.…”
Section: Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…(33) einstein (São Paulo). 2020;18:1-14 Chung et al (28) Teaching hospital in Malaysia Ali et al (29) Community pharmacies in the United Kingdom Xin et al (38) Tongde Hospital, Hangzhou province, China As regards performance bias, no studies reported blinding to pharmacist's activities, and exchange of information between participants may have occurred in 14 studies conducted in a single setting, except the multicenter study by Siaw et al (33) That trial was thought to involve high risk of bias regarding blinding of participants and professionals, since participants in the Control Group were able to consult pharmacists, if required. (34) As regards detection bias, only one study reported blinding of raters, who were therefore unaware of groups being evaluated.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Ten studies were included in the metaanalysis, (21,(27)(28)(29)32,34,(36)(37)(38)(39) all of them with high heterogeneity for all endpoints (I 2 97% to 99%; p<0.001). The efficacy of pharmaceutical care to promote reduction of SBP, HbA1c, fasting glucose and TG levels and increase of HDL levels was demonstrated in all studies, in spite of significant heterogeneity.…”
Section: Heterogeneity Analysismentioning
confidence: 99%
“…Wishah et al [21] À1.7 AE 1.24 52 À0.3 AE 1.12 54 Chen et al [22] À0.83 AE 1.31 50 0.43 AE 1.3 50 Xin et al [26] À2.36 AE 2.14 114 À0.77 AE 1.71 113 Butt et al [28] À1.19 AE 1.35 33 À0.38 AE 1.31 33 Cani et al [20] À0.57 AE 1.26 34 À0.08 AE 1.34 36 Chung et al [29] À1.4 AE 1.1 120 À0.2 AE 1.42 121 Mahwi et al [23] À2.33 AE 1.63 62 À0.47 AE 2.17 61 Ali et al [18] À1.6 AE 1.34 23 À0.6 AE 0.75 23 Chan et al [27] À1.57 AE 1.50 51 À0.40 AE 1.19 54 Jacobs et al [17] À1.8 AE 1.03 72 À0.8 AE 1.24 92 Farsaei et al [24] À1.8 AE 1.4 86 0.1 AE 1 8 6 Mehuys et al [19] À0.6 AE 1.30 153 À0.1 AE 0.96 135 Sriram et al [25] À1.71 AE 0.5 60 À0.72 AE 0.39 60 The present systematic review showed that RCTs with follow-up of >6 months report more significant mean reductions in HbA1c levels than RCTs with shorter follow-up. This suggests that better control is afforded through sustained PC interventions.…”
Section: Patient Numbersmentioning
confidence: 99%
“…9) Furthermore, Xin et al showed that adherence and clinical outcomes were improved by hospital pharmacists providing pharmaceutical care working together with doctors. 10) Moreover, patient education about type 2 diabetes, prescription medications and necessary lifestyle changes in the diabetes outpatient department leads to a decrease of HbA1c level. 11) American pharmacists have more responsibilities than Japanese pharmacists.…”
Section: Introductionmentioning
confidence: 99%